Edugame of Traditional Dance of Indonesia with Augmented Reality - Ustia, Nurul; Sudarmilah, Endah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
Traditional dance is one of the results of culture form of dance for generations by people in Indonesia. Currently, we require new innovations to attract people and students, in recognizing the traditional dance of Indonesia. Therefore, the writer made augmented reality edugame to attract interest in learning and developing the traditional dance of Indonesia. The method used was SDLC (System Development Life Cycle) method on waterfall model. Augmented reality application on Edugame to Identify Traditional Dance of Indonesia was able to teach movement and dance information learned by the students described in this paper.